MENGANALISIS PEMANFAATAN METODE FAST TRACK LEGISLATION DALAM UNDANG-UNDANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Julian Immanuel Bonahuta (2023)
The establishment of laws and regulations in Indonesia has been regulated in Law Number 12 of 2011 concerning the Establishment of Laws and Regulations in Indonesia, Law 15 of 2019 concerning Amendments to Law 12 of 2011, and finally Law 13 of 2022 concerning the 2nd Amendment. During the process until the issuance of changes to the Law on the Establishment of Laws and Regulations in Indonesia, no one specifically regulates the Fast Track Legislation method, but in its own implementation in Indonesia there are several laws that use fast legislation channels in the last 5 years such as the KPK Law, the Constitutional Court Law, the Job Creation Law. Although there is actually also a mechanism in making laws quickly in Indonesia, namely the establishment of government regulations in lieu of laws (Perppu) where the goal is to respond to a compelling emergency but we can also analyze the opportunities for the use of the Fast Track Legislation method in the Law on the Establishment of Laws and Regulations and what criteria are applied specifically if the Fast Track Legislation method is applied in Indonesia.